Former Haitian first lady seeks to declassify documents related to her husband's assassination - Ducrepin, Sindy (Voice of America, 2025)
Martine Moise, former first lady of Haiti, appealed to U.S. President Donald Trump to declassify documents related to the assissination of her husband, Haitian President Jovenel Moise.
Haiti